“ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Kabupaten/Kota Provinsi Jawa Tengah Tahun 2014-2016)” - Nasriyatun, 14.05.52.0045; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This study is examines and analyze the effect of size of the local goverment , age of the local government, find audite, functional diferentiation, intergovermental revenue, and the leverage on the level of disclosure LKPD Regency / City in Central Java Province. This study population was District / City of Central Java Province during the years 2014-2016 that have been audited by BPK. The sample used is 105 local government financial statements are all the population sampled. This research data analysis methods using the multiple linear regression analysis by SPSS 19. The result showed that find audite and leverage have significant positive effect on the level of disclosure LKPD. Intergovermental Revenue and Functutional Diferentiation have significant negative effect on the level of disclosure LKPD. While variabels size of local goverment, and age of local government does not affect the level of Disclosure LKPD. Keywords: Level of Disclosure LKPD, Size of local government, Age of Local Government, Find Audite, Functutional Diferentiation, Intergovermental Revenue and Leverage.